Pengembangan media pembelajaran matematika berbasis macromedia flash pada materi teorema pythagoras untuk siswa Sekolah Menengah Pertama - Azila, Aida; Sari, Riska Novia; Arcat (Jurnal Pendidik Indonesia, 2022)
This study aimed to produce valid Macromedia flash-based mathematics learning media on the Pythagorean theorem material. The type of research used was research development (R&D), which consists of three development stages: defining, designing, and development. The instrument used in this study was a validation questionnaire. The validation questionnaire sheet includes didactic aspects, content, language, and display. The results of the research on the development of Macromedia flash-based mathematics learning media based on the validity test of Macromedia flash-based mathematics learning media that have been carried out on three validators and various revisions and improvements, the average score of the results of the validity of Macromedia flash-based mathematics learning media was 3.37 with a very valid category. So the Macromedia flash-based mathematics learning media was very valid.